More powerful dysregulation of Helicobacter pylori East Asian-type CagA on intracellular signalings - Xiaofei Ji; Zekun Sun; Hao Wu; Jianhui Zhang; Shuzhen Liu; Xinying Cao; Bin Wang; Feifan Wang; Ying Zhang; Boqing Li; Jiankai Feng; Huilin Zhao (BMC Microbiology)
Abstract Background Chronic infection by Helicobacter pylori strains expressing cytotoxin-associated gene A (CagA) are the strongest risk factor for gastric cancer. CagA can be classified into East Asian-type and Western-type (CagAE and CagAW), with CagAE being more closely associated with gastric cancer. This study aimed to investigate the impact of CagAE on intracellular signaling pathways to explain its high oncogenicity. Results Mutant H. pylori strains expressing either CagAE or CagAW were generated by transforming CagAE/W-expression plasmid into CagA-deleted G27 strain (G27ΔCagA). In human gastric epithelial cells (GES-1) infection, CagAE induced more severe cytopathic changes, including higher interleukin-8 (IL-8) secretion, reduced cell viability, more pronounced “hummingbird phenotype” alterations, and increased cell migration and invasion compared to CagAW. Transcriptome analysis revealed that CagAE had a stronger effect on the up-regulation of key intracellular processes, including tumor necrosis factor-ɑ (TNF-ɑ) signal pathway via nuclear factor kappa-B (NF-κB), inflammatory response, interferon-γ (IFN-γ) response, hypoxia, ultraviolet (UV) response, and Kirsten Rat Sarcoma Viral Oncogene Homolog (KRAS) signaling. A significant upregulation of hypoxia-related genes was a notable feature of CagAE. GES-1 cells infected with CagAE exhibited more severe intracellular hypoxia and higher levels of reactive oxygen species (ROS) than those infected with CagAW. Inhibition of hypoxia-inducible factor-1α (HIF-1α), which blocks hypoxia signaling, mitigated CagAE-induced cell migration, emphasizing the role of hypoxia in mediating CagAE effects. Conclusions The study provides transcriptome evidence of CagA-associated intracellular regulation during H. pylori infection, demonstrating that CagAE exerts stronger effects on intracellular signaling than CagAW. These findings offer insights into the heightened carcinogenic potential of CagAE in H. pylori-induced gastric cancer.